Shakespeare : his life and works - Downer, Leslie Dunton and Allan Riding (London Dorling Kindersley Limited, 2021)
"A new edition of the comprehensive guide to Shakespeare, exploring his life and works, and his enduring legacy, in a stunning gift format. Unravel the history, themes, and language of Shakespeare's plays, poems, and sonnets with this beautifully illustrated guide to his life and works. Comedy and romance, history, and tragedy, Shakespeare's canon has it all. Some 400 years after they were written and first performed, his works still remain fresh and relevant today. Shakespeare: his life and works is an accessible and lavishly illustrated celebration of the Bard himself and his 39 plays, great sonnets, and narrative poems. Themes, plots, characters, and language are brought to life with act-by-act plot summaries, resumes of main characters, and in-depth analysis of Shakespeare's use of, and influence on, the English language. Entries also explore Shakespeare's plays, poems, and sonnets in the context of his life and the world of Elizabethan and Jacobean theatre, and reveal his sources and inspirations, further enriching your experience of his work, be it on the page, stage, or screen. Shakespeare: his life and works is the perfect gift for existing Shakespeare fans, and anyone looking to find out more about the work of the world's most celebrated playwright"--Publisher's description